BİR GEÇMİŞ ZAMAN EFENDİSİ: MÜKRİMİN HALİL YİNANÇ - Mustafa ORAL (Turkish History Education Journal, 2015)
Mükrimin Halil Yinanç is one of the remarkable personages of modern history writing in the period from Constitutional Monarchy to Republic, in Turkey. Describing Mükrimin Halil Yinanç‘s intellectual milieu vis-à-vis his position within this environment besides his contribution to historiography, we meticulously examined the conditions at that period, the environment in Istanbul where Mukrimin Halil Yinanç grew up in the early Republican Period and his relationship with this environment. Since Mukrimin Halil Yinanç is a member of a family related to oldest Turkmen tribes in Elbistan, with longestablished Muslim traditions, he belongs to an environment determined by a conservative culture. In 1916, he studied history at the Faculty of Literature in Istanbul Darulfünun; when he graduated from this faculty (1919), he became a student in Mekteb-i Mülkiye (The School of Political Science). After his graduation (1921), he was appointed to Davut Pasha Secondary School as a teacher of history. In addition to this task, he undertakes a mission in